ARTISTRY AND ENTERTAINMENT: CLASS AND RACE NAVIGATIONS OF DUKE ELLINGTON AND LOUIS ARMSTRONG - (:unkn) unknown (My University, 2024)
This thesis examines the early careers of Duke Ellington and Louis Armstrong and holds them against the larger cultural, social, and economic landscape of the United States during the early twentieth century. Black Americans had been freed from slavery by Emancipation, but the rise of the racist Jim Crow laws, starting in the late 1880s, had stripped away many of their freedoms once again and kept them in a lower caste of the American system. On top of Jim Crow, the United States was facing Prohibition laws, the Great Depression, and World War I, creating a tumultuous landscape for any citizen, let alone Black Americans. Ellington and Armstrong had also worked their way to national fame against the odds, and this thesis shows the paths they took to attain their lasting legacies. Both are examined through case studies, with Ellington finding success through gaining relative respectability in white culture and his dedication to his artistry, and Armstrong finding his through the relationships he garnered in his early career that allowed him to hone and craft his audience-oriented performance philosophy. These case studies are preceded by a chapter describing the intricacies of American culture during this time, and the greater efforts of Black uplift that are interwoven into these two musicians’ lives. I will seek to paint a well-developed portrait of the American landscape of the early twentieth century through the lives of prominent Black musicians of this era.